Analysis of the age of elite female tennis athletes at their peak competitive ability - Guo, X.Y.; Li, N. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: In recent years, the age of world elite female tennis athletes during their competitive years has changed. This paper aimed to study and analyse the age distribution of the top 50 tennis players. The object of the study was to improve the scientific basis of training in this event, promote the study of longevity as a tennis player, and provide reference and guidance for the development of tennis. Methods Review of literature, collection and analysis or record data. Results The results indicated that the age that female tennis players become professional athletes was: 13 (19.4%), 14 (41.7%), 15-16 (20.8%), >16 (18.1%). On average female tennis players reached their best competitive level at age 21.5 years, with a range from 16 to 29 years. Tennis players are required to have a certain level of aerobic capacity. The female tennis players in this study achieved optimal aerobic metabolism ability between the ages of 21 to 23. From the distribution shown in Table 2, the age at the best competitive ability for the world elite female tennis players ranges from 18 to 26. Conclusions The age at which world elite female tennis athletes achieve their best competitive level is within the range of 18 to 26. Based on the present findings, knowledge about how to prolong an athletes` competitive sport life so as to enable a second competitive period is an issue that coaches, athletes and researchers should try to address.